The Potential of Digital Preservation in Neurajah Oral Traditions as an Effort to Preserve Local Culture - Indah Fajarini; Joko Hariadi; Muhammad Taufik Hidayat; Prima Nucifera; Nuriana Nuriana (Widyantara, 2026)
This study examines the documentation and digital preservation of Neurajah, a traditional healing prayer and medicinal antidote in East Aceh, which is currently threatened by globalization and technological advancements. Utilizing a descriptive qualitative approach based on post-positivist philosophy, this literature study synthesized secondary sources from platforms such as Google Scholar, Semantic Scholar, SpringerLink, and ResearchGate using specific inclusion and exclusion criteria. The results indicate that while the Neurajah tradition holds significant cultural value, public interest and understanding have declined due to the dominance of modern knowledge. The study establishes a systematic framework for narrator selection, documents the core knowledge embedded in the tradition, and evaluates the implementation and challenges of using digital media as a sustainable tool for local cultural preservation. Studi ini meneliti dokumentasi dan pelestarian digital Neurajah, sebuah doa penyembuhan tradisional dan obat penawar racun di Aceh Timur, yang saat ini terancam oleh globalisasi dan kemajuan teknologi. Dengan menggunakan pendekatan kualitatif deskriptif berdasarkan filsafat post-positivis, studi literatur ini mensintesis sumber sekunder dari platform seperti Google Scholar, Semantic Scholar, SpringerLink, dan ResearchGate menggunakan kriteria inklusi dan eksklusi tertentu. Hasil penelitian menunjukkan bahwa meskipun tradisi Neurajah memiliki nilai budaya yang signifikan, minat dan pemahaman masyarakat telah menurun karena dominasi pengetahuan modern. Studi ini menetapkan kerangka kerja sistematis untuk pemilihan narator, mendokumentasikan pengetahuan inti yang tertanam dalam tradisi tersebut, dan mengevaluasi implementasi dan tantangan penggunaan media digital sebagai alat yang berkelanjutan untuk pelestarian budaya lokal.